Predictors of lung recurrence and disease-specific mortality after pulmonary metastasectomy for soft tissue sarcoma. (June 2021) - Tetta, Cecilia; Rocca, Michele; Salone, Mariacristina; Longhi, Alessandra; Ferrari, Cristina; Londero, Francesco; Parise, Gianmarco; Parise, Orlando; Giugliano, Antonio; Maessen, Jos G.; La Meir, Mark; Gelsomino, Sandro
Abstract: Background: We identified prognostic factors in a 30-year series of STS treated at a single Institution, using an advanced statistical approach. Methods: From June 1988 to July 2019, 164 patients were referred to Rizzoli Orthopedic Hospital, Bologna, Italy) for STS lung metastasectomy (LMTS). The endpoints were lung metastasis recurrence (LMR) and lung metastasis-specific mortality (LMSM). The analysis included directed acyclic graphs, cubic splines, and a competing risk model in order to minimize bias. Results: The 10- and 15- year LMR cumulative incidence were 0.77 (0.76–0.78) whereas 10- and 15- year freedom from LMSM were 0.60 [0.51–0.70] and 0.56 [0.47–0.67], respectively. The malignant peripheral nerve sheath tumor (MPNST) histotype (SHR 4.12 [2.05–8.27]), a disease-free interval (DFI) up to 68 months (HR from 2 [1.7–2.2] to 1.5 [1.1–1.9]) and a LM size ≥4 mm (3.1 [2.1–4.4]) predicted LMR. Myxofibrosarcoma (HR 2.52[1.64–3.86]), synovial sarcoma (2.53[1.22–5.23]), adjuvant chemotherapy (2.01[1.11–3.61]), DFI between 2 months and 20 months (HR from 1.5 [1.1–2.3] to 1.3 [1.1–1.7] and primary tumor size a primary tumor size comprised between 3.6 cm and 10 cm predicted LMSM. A sharp increase in LMSM was observed with a tumor size from ≥20 cm. Conclusions: Our analysis corrected by potential confounders allowed us to identify specific histotypes and DFI intervals as predictors of both LMR and LMSM. Tumor size adjuvant chemotherapy adversely affected LM-related survival. Our findings need to be confirmed by larger randomized studies. Graphical abstract: Image 1 Highlights: Malignant peripheric nerve sheath tumor rises lung metastasis recurrence in STS. Myxofibrosarcoma and synovial sarcoma increase lung metastasis-specific mortality. The risk of lung recurrence is high up to 68 month-DFI. A DFI ranging between 2 and 20 months reduces lung metastasis-specific mortality. Metastasis size ≥ 4 mm dramatically increase the risk of lung recurrence.